International corporate governance - John, Kose.; Makhija, Anil K.; Ferris, Stephen P. (Bingley, U.K. : Emerald, 2015)
Advances in Financial Economics, volume 18, will present research on corporate governance both in the US and globally. Papers will deal with the role played by boards of directors, internal organization design and governance mechanisms, franchise agreements, the effect of regulation and policy, the market for corporate control, and strategic alliances. The volume will aim at providing a deeper understanding of corporate governance practices, trends, innovations and challenges using international data.
Ownership structure and power : evidence from US corporations / Nilanjan Basu, Imants Paeglis, Mohammad Rahnamaei -- Changes in controlling shareholders' holdings : do they entail financial tunneling? / Menachem (Meni) Abudy, Beni Lauterbach -- Devolution of the republican model of Anglo-American corporate governance / Robert Wright -- Toward a better measure of bank corporate governance / James McNulty, Aigbe Akhigbe -- Corporate political connections and the IPO process : the benefits of politically-connected board members and managers / Reza Houston, Stephen Ferris -- Internal corporate governance : the role of residual income in divisional allocation of funds / Dobrina Georgieva -- Ownership matters : the capital structure of private firms / William McCumber -- Investor protections, capital markets, and economic growth : the African experience / Bill Francis, Iftekhar Hasan, Eric Ofori.
Print version record
Keywords: Corporate governance; Business & Economics -- Corporate Governance; Economics